2016
DOI: 10.1038/srep21714
|View full text |Cite
|
Sign up to set email alerts
|

A novel biliary stent coated with silver nanoparticles prolongs the unobstructed period and survival via anti-bacterial activity

Abstract: Symptomatic biliary stricture causes life-threatening complications, such as jaundice, recurrent cholangitis and secondary biliary cirrhosis. Fully covered self-expanding metal stents (FCSEMSs) are gaining acceptance for treatments of benign biliary stricture and palliative management of malignant biliary obstructions. However, the high rate of FCSEMS obstruction limits their clinic use. In this study, we developed a novel biliary stent coated with silver nanoparticles (AgNPs) and investigated its efficacy bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 36 publications
(60 reference statements)
0
27
0
Order By: Relevance
“…An in vivo animal study revealed that coating of a polyurethane stent with silver nanoparticles inhibited bacterial adhesion for 7 days 16 . In another study, a silver-coated biliary plastic stent prolonged the unobstructed period, owing to its antibacterial activity 17 . These results suggested that coating of plastic stents with silver nanoparticles resulted in the release of nano-silver, which inhibited bacterial growth and prolonged stent patency.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…An in vivo animal study revealed that coating of a polyurethane stent with silver nanoparticles inhibited bacterial adhesion for 7 days 16 . In another study, a silver-coated biliary plastic stent prolonged the unobstructed period, owing to its antibacterial activity 17 . These results suggested that coating of plastic stents with silver nanoparticles resulted in the release of nano-silver, which inhibited bacterial growth and prolonged stent patency.…”
Section: Discussionmentioning
confidence: 97%
“…To prevent biofilm formation on biliary stents, several in vitro and in vivo animal studies have reported the bactericidal efficacy of silver-coated plastic stents due to the release of silver ions, which suggested prolonged stent patency, but the clinical efficacy has not been evaluated 13 14 15 16 17 . Recently, the concept of using silver nanoparticles (AgNPs) as an antimicrobial agent in a plastic stent has been studied 18 19 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Darren and Chithrani [6] presented a comprehensive review on applications of nanoparticle in medicine by offering view point on visualization, diagnosis and treatment of disease under a variety of nanoparticles. Yang, et al [7] developed a novel biliary stent.…”
Section: Study Of Nanoparticles At Atomic Level Is Vital To Implant Tmentioning
confidence: 99%
“…Darren & Chithrani [6] presented a comprehensive review on applications of nanoparticle in medicine by offering view point on visualization, diagnosis and treatment of disease under a variety of nanoparticles. Yang et al [7] developed a novel biliary stent.…”
Section: Introductionmentioning
confidence: 99%